Flexural Behavior of Reinforced RAC Beams Exposed to 1000°C Fire for 18 Hours - Buller, A. H.; Oad, M.; Memon, B. A. (Engineering, Technology & Applied Science Research, 2019)
In order to meet the socio-economic demands around the globe, construction industry not only consumes concrete at a very fast pace but also yields huge amounts of construction and demolishing waste. The phenomenon gives rise to environmental issues due to production of concrete ingredients and due to dumping of the waste. Therefore, one of the solutions is the production of green concrete utilizing demolished waste. This research work studies the effect of prolonged fire (18 hours) on the flexural behavior of reinforced concrete–recycled aggregate beams. The beams were using 50% replacement of natural coarse aggregates with demolished concrete. The beam samples were cast as both normal and rich mix concrete and were cured for 28 days. After curing, the beams were exposed to fire at 1000°C in a purpose made oven, followed by testing in a universal load testing machine under central point load. The test results show that the proposed beams (cast with rich mix) exhibited about 22% reduction in flexural strength. The failure mode of the beams was observed as shear failure.